2017
DOI: 10.3389/fimmu.2017.00174
|View full text |Cite
|
Sign up to set email alerts
|

Follicular T Cells from smB− Common Variable Immunodeficiency Patients Are Skewed Toward a Th1 Phenotype

Abstract: Germinal center follicular T helper (GCTfh) cells are essential players in the differentiation of B cells. Circulating follicular T helper (cTfh) cells share phenotypic and functional properties with GCTfh cells. Distinct subpopulations of cTfh with different helper capabilities toward B cells can be identified: cTfh1 (CXCR3+CCR6−), cTfh2 (CXCR3−CCR6−), and cTfh17 (CXCR3−CCR6+). Alterations in cTfh function and/or distribution have been associated with autoimmunity, infectious diseases, and more recently, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
54
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(60 citation statements)
references
References 54 publications
5
54
1
Order By: Relevance
“…As explained earlier, TFH can be divided into two subsets: the non-efficient helper TFH1 and the efficient helpers TFH2 and TFH17. Interestingly, we (75) and others (77,78,80) highlight a specific increase of the circulating TFH1 only in non-infectious CVID patients. Moreover, CXCR3 + (75) or Tbet + (78) cells were amplified in secondary lymphoid organs of CVID patients, suggesting that the blood observations reflect the GC counterpart.…”
Section: Tfh and Cvidsupporting
confidence: 53%
See 2 more Smart Citations
“…As explained earlier, TFH can be divided into two subsets: the non-efficient helper TFH1 and the efficient helpers TFH2 and TFH17. Interestingly, we (75) and others (77,78,80) highlight a specific increase of the circulating TFH1 only in non-infectious CVID patients. Moreover, CXCR3 + (75) or Tbet + (78) cells were amplified in secondary lymphoid organs of CVID patients, suggesting that the blood observations reflect the GC counterpart.…”
Section: Tfh and Cvidsupporting
confidence: 53%
“…Interestingly, our group (75) and others (76)(77)(78) observed an increase of circulating TFH (memory CXCR5 + CD4 T cells) in CVID patients harboring non-infectious complications. Moreover, TFH expressing PD-1 were present at higher levels in CVID patients with complications (75)(76)(77)(78). Patients classified as smB − based on the EUROClass have <2% of switched memory B cells among circulating CD19 + cells (12).…”
Section: Tfh and Cvidmentioning
confidence: 70%
See 1 more Smart Citation
“…Altered frequencies and/or the suppressive capacity of cTfr cells have been elucidated in a multitude of AIDs, including systemic AIDs and organ‐specific AIDs (shown in Table ). Systemic AIDs involve rheumatoid arthritis (RA), systemic lupus erythematosus (SLE), Sjögren's syndrome (SS), ankylosing spondylitis (AS), IgG4‐related disease (IgG4‐RD) and common variable immune deficiency (CVID) . Organ‐specific AIDs involve multiple sclerosis (MS), myasthenia gravis (MG), Hashimoto's thyroiditis (HT), primary biliary cholangitis (PBC), type 1 diabetes (T1D) and ulcerative colitis (UC) .…”
Section: Tfr Cells In Human Diseases and Animal Modelsmentioning
confidence: 99%
“…Systemic AIDs involve rheumatoid arthritis (RA), [58][59][60][61][62] systemic lupus erythematosus (SLE), 33,63-65 Sj€ ogren's syndrome (SS), 14,66,67 ankylosing spondylitis (AS), 68 IgG4related disease (IgG4-RD) 69 and common variable immune deficiency (CVID). 70 Organ-specific AIDs involve multiple sclerosis (MS), 15,71,72 myasthenia gravis (MG), [73][74][75] Hashimoto's thyroiditis (HT), 76 primary biliary cholangitis (PBC), 77 type 1 diabetes (T1D) 78 and ulcerative colitis (UC). 79 It is also demonstrated that when the regulatory capacity of Tfr cells is impaired, the expansion of Tfr cells is accompanied by the development of autoimmunity in mice.…”
Section: Tfr Cells In Autoimmune Diseasesmentioning
confidence: 99%